2015
DOI: 10.1002/jts.22005
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer Diagnosis and Treatment as a Traumatic Stressor in DSM‐IV and DSM‐5: Prevalence and Relationship to Mental Health Outcomes

Abstract: Little research has examined how lung cancer survivors whose cancer experience met the Diagnostic and Statistical Manual of Mental Disorders (DSM) traumatic stressor criterion differ with regard to posttreatment mental health status from survivors whose cancer experience did not. No research of which we are aware has examined the impact of the revised DSM-5 traumatic stressor criterion on this question. Non-small-cell (NSC) lung cancer survivors (N = 189) completed a telephone interview and questionnaire asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 33 publications
(41 reference statements)
0
16
1
Order By: Relevance
“…60 Although findings regarding the relationship between cancer-related post-traumatic growth and cancer-related PTSD have been inconsistent, 9,61,62 the perceived threat posed by cancer might set the stage for both to occur. 24,26 …”
Section: Conceptual Methodological and Diagnostic Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…60 Although findings regarding the relationship between cancer-related post-traumatic growth and cancer-related PTSD have been inconsistent, 9,61,62 the perceived threat posed by cancer might set the stage for both to occur. 24,26 …”
Section: Conceptual Methodological and Diagnostic Issuesmentioning
confidence: 99%
“…Mehnert and Koch 25 found that cancer was a traumatic stressor for 69 (54%) of 127 patients with breast cancer. Andrykowski and colleagues 26 found that of 189 survivors of lung cancer, 70 (37%) patients endorsed diagnosis and treatment as a traumatic stressor using DSM-IV criteria, and 108 (57%) patients did so using DSM-5 diagnostic criteria. Similarly, Mulligan and colleagues 27 found that nearly half (70 of 170 patients) of a predominantly male sample of veterans with heterogeneous cancer types endorsed cancer as a traumatic stressor.…”
Section: Cancer As a Traumatic Stressormentioning
confidence: 99%
“…This was directly contradictory to Tedeschi and Calhoun's (2004) study and Andrykowski's (2015) corroboration and elaboration that trauma is not only a factor in posttraumatic growth, but is necessary. This study focused on the number of events that the person experienced and not the severity--a possible factor in the results found.…”
Section: Resultscontrasting
confidence: 56%
“…Andrykowski et al elaborates on Tedeschi and Calhoun's findings, stating that trauma is needed to trigger post-traumatic emotional growth and that greater growth was found consistently with greater negative stress (Andrykowski et al, 2015). An article by Zoellner & Maercker (2006) repeats this finding.…”
mentioning
confidence: 97%
“…Therefore, in this scenario, without the psychological reaction to being diagnosed with lung cancer, 14 we hypothesize that these patients may be less likely to develop PTSD, depending on what type of illness they believe they are suffering from (whether or not this is a traumatic stressor). Andrykowski et al 47 demonstrated that 37% (n = 70/189) of their patients with lung cancer (mean ± SD of 16 ± 2 months postdiagnosis) recognized that a lung cancer diagnosis and treatment was a traumatic stressor for them (based on meeting the DSM-IV stressor criteria). 47 Unfortunately, we did not collect details of the diagnosis that the patient was given—that is, if they were told that they had a respiratory illness or another condition for which they were undergoing treatment—and although the traumatic event does not need to involve death to satisfy PTSD criteria (ie, it can be a threat to physical integrity), 14 we do not know how this theoretical threat may be perceived by the patient.…”
Section: Discussionmentioning
confidence: 99%